1999
DOI: 10.1523/jneurosci.19-21-09663.1999
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Transporters Contribute to the Time Course of Synaptic Transmission in Cerebellar Granule Cells

Abstract: Transporters are thought to assist in the termination of synaptic transmission at some synapses by removing neurotransmitter from the synapse. To investigate the role of glutamate transport in shaping the time course of excitatory transmission at the mossy fiber-granule cell synapse, the effects of transport impairment were studied using whole-cell voltage-and currentclamp recordings in slices of rat cerebellum. Impairment of transport by L-trans-pyrrolidine-2,4-dicarboxylate (PDC) produced a prolongation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 68 publications
3
83
0
Order By: Relevance
“…In addition, maturation of glutamate reuptake would almost certainly influence the decay kinetics of glutamate receptors (Overstreet et al, 1999), whereas we show that AMPA decay remains constant throughout maturation in all cell types (Fig. 4).…”
Section: Underlying Mechanisms For Increases In the Ampa:nmda Ratiomentioning
confidence: 64%
“…In addition, maturation of glutamate reuptake would almost certainly influence the decay kinetics of glutamate receptors (Overstreet et al, 1999), whereas we show that AMPA decay remains constant throughout maturation in all cell types (Fig. 4).…”
Section: Underlying Mechanisms For Increases In the Ampa:nmda Ratiomentioning
confidence: 64%
“…For example, the glutamate transporter, EAAT4, is highly enriched on Purkinje cell spines (66) where it is thought to modulate postsynaptic excitation (67,68). Similarly, EAAC1 is associated with dendritic spines and shafts in the CA1 region of the hippocampus (57).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that used the electrophysiological method have shown that inhibition of GT activity may not prolong significantly the single stimulus-induced excitatory postsynaptic glutamate-mediated currents, but it does so if the stimulus is repetitive and excessive (Overstreet et al, 1999), a condition that is encountered after peripheral nerve injury (Wall et al, 1974;Seltzer et al, 1991). In this regard, enhancing GT uptake activity by the positive GT activity regulator riluzole would be expected to reduce glutamate excitation regardless of changes in GT expression.…”
Section: Possible Mechanisms Of Gt Changes After CCImentioning
confidence: 99%